The Use of Total Physical Response (TPR) Activities for Teaching Listening to Young Learners - Inti Englishtina (STKIP Al Hikmah Surabaya, 2019)
Although infants are not speaking, they are still active users of the language because they are physically responding to what has been said. As teachers of second and foreign-language learners, it is useful to consider the listening skills that are taught to children learning English as a first language. This article examines the use of Total Physical Response (TPR) activity as one of the activities for teaching listening to young learners. The article begins with the concept of Total Physical Response (TPR) activity, and continues with various ways of using this activity for teaching listening to young learners. In addition, the effectiveness of this activity is also discussed.